The effect of microbiome-modulating probiotics, prebiotics and synbiotics on glucose homeostasis in type 2 diabetes: A systematic review, meta-analysis, and meta-regression of clinical trials - Pradipta Paul (12628162) (2022)
Aim/hypothesis The globally escalating diabetes epidemic is responsible for significant morbidity and mortality. Microbiome-modulating nutraceuticals have been investigated for their potential to restore metabolic and floral homeostasis in type 2 diabetic patients. Methods A systematic review, meta-analyses and meta-regressions were conducted to investigate the effect of probiotics, prebiotics, and synbiotics on various biomarkers of glucose homeostasis based on a multi-database search of clinical trials published through April 10, 2022. Data was pooled using random effects meta-analyses and reported as mean differences with 95% confidence intervals (CIs), followed by univariate linear model meta-regression. Results Data from 68 trial comparisons across 58 studies (n = 3835) revealed that, compared to placebo/control group, administration of pro/pre/synbiotics was associated with statistically significant changes in fasting plasma glucose (−12.41 mg/dl [95% CI: −15.94; −8.88], p 0.0001), glycated hemoglobin (−0.38% [95% CI: −0.47; −0.30], p 0.0001), fasting insulin (−1.49 µU/mL [95% CI: −2.12; −0.86], p 0.0001), HOMA-IR (−0.69 [95% CI: −1.16; −0.23], p = 0.0031) and QUICKI (0.0148 [95% CI: 0.0052; 0.0244], p = 0.0025), but not C-peptide (−0.0144 ng/mL [95% CI: −0.2564; −0.2275], p = 0.9069). Age, baseline BMI, baseline biomarker value, pro/prebiotic dosage, trial duration, nutraceutical type, and recruitment region significantly affected the potential of pro/pre/synbiotics use as personalized diabetes adjunct therapy. Lastly, we discuss unexplained observations and directives for future trials, with the aim of maximizing our understanding of how microbiome-modulating nutraceuticals can treat various metabolic diseases. Conclusions Pro/pre/synbiotic supplementation improved glucose homeostasis in diabetic patients. Our results support their potential use as adjunct therapy for improving glycemia and insulinemia alongside pharmacological therapeutics. Other Information Published in: Pharmacological Research License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.phrs.2022.106520